Ultrasound-Assisted Extraction of Polysaccharides from Mulberry Leaves Using Response Surface Methodology: Purification and Component Identification of Extract - Teng Wang; Xiaolin Zou; Hong Zhang; Jiwen Li; Xiaoming Peng; Ruijun Ju; Zhaojun Jia; Zhenguo Wen; Cuiqing Li (Molecules)
In this study, an ultrasonic-assisted procedure for the extraction of mulberry leaf polysaccharides (MLPs) was investigated using response surface methodology with a 29-run Box–Behnken design. Four factors were investigated, and it was found that the factors influencing the process, in order of significance, were the extraction temperature > liquid-to-material ratio > ultrasonic power. Considering practical conditions, the parameters were adjusted to a liquid-to-material ratio of 16:1 mL/g, extraction time of 58 min, extraction temperature of 65 °C, and ultrasonic power of 500 W. Under these conditions, the yield of MLPs was 14.47%, which is close to the predicted value, indicating that the extraction process optimized by response surface methodology (RSM) is feasible. The separation and purification effects of macroporous resin and activated carbon on MLPs were investigated, with the D152 resin being considered the most suitable choice. The optimal separation conditions were found to be a sample concentration of 0.5 g/mL and an optimal flow rate of 1 mL/min. Thin-layer chromatography and infrared spectroscopy revealed that polysaccharides extracted from mulberry leaves are primarily composed of rhamnose, xylose, and arabinose. In conclusion, this study successfully optimized the ultrasonic-assisted extraction process of MLPs through response surface methodology, determined the optimal parameter combination, and verified its efficiency and stability. Under the optimal conditions obtained for ultrasonic-assisted extraction, the yield of MLPs is significantly higher than that reported in the previous literature. The decolorization process of crude mulberry leaf polysaccharide extract was also investigated, and the purified MLPs have clear monosaccharide composition and structural characteristics, providing a theoretical basis and technical support for their application in functional food or drug development.